REAL-WORLD SURVEY ON INSULIN INJECTION TECHNIQUES AMONG PEOPLE WITH DIABETES IN SEMI-URBAN AND VILLAGE POPULATION IN KERALA - B, Jayakrishnan; Sankar, Prasanth (Journal of the ASEAN Federation of Endocrine Societies, 2022)
OBJECTIVE The success of insulin therapy in diabetes depends on proper storage and correct injection technique. The objective of this study is to assess the current insulin injection technique among patients with diabetes mellitus in semi-urban and village population in Kerala. METHODOLOGY This observational study was conducted from June to December 2021 in Tirur and Pathanamthitta, Kerala. A total of 140 participants aged 25 to 60 years, using insulin pen or vial for at least 3 months were recruited. A survey questionnaire on key insulin injection practices was administered. RESULTS The abdomen was the most common (57.14%) site of insulin injection. Injection site rotation was followed by 92.85%. The practice of handwashing and cleaning of the injection site was practiced by 110 (78.57%) & 105 (75%), respectively. A total of 135 (96.42%) subjects were using the needle more than once. Majority (85.71%) were storing insulins at proper temperature. Pain and swelling at the injection site were reported by 52.14 % and 7.14%, respectively. The majority of patients (96.42%) threw the needle and syringes directly into the garbage and public drainage system. CONCLUSION Our study identified a significant gap between insulin administration guidelines and current insulin injection practice. Hence, diabetes education and counselling about proper insulin injection techniques should be provided to people with diabetes and their caregivers.